2017
DOI: 10.1371/journal.pone.0183177
|View full text |Cite
|
Sign up to set email alerts
|

Expression optimization of a cell membrane-penetrating human papillomavirus type 16 therapeutic vaccine candidate in Nicotiana benthamiana

Abstract: High-risk human papillomaviruses (hr-HPVs) cause cervical cancer, the fourth most common cancer in women worldwide. A HPV-16 candidate therapeutic vaccine, LALF32-51-E7, was developed by fusing a modified E7 protein to a bacterial cell-penetrating peptide (LALF): this elicited both tumour protection and regression in pre-clinical immunization studies. In the current study, we investigated the potential for producing LALF32-51-E7 in a plant expression system by evaluating the effect of subcellular localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…In summary, we have shown how LALF 32-51 -E7 and LALF-E7-GFP polypeptides form PB-like structures when targeted to chloroplasts, which are more concentrated and abundant than for the cytoplasmic versions. These results could explain why LALF 32-51 -E7 accumulated to much higher levels when targeted to the chloroplasts than when localized in the cytoplasm in our vaccine production feasibility study (Yanez et al, 2017). This study was a proof of concept that confirms the importance of subcellular localization, and which further highlights that chloroplasts are a useful compartment to which to target recombinant proteins.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In summary, we have shown how LALF 32-51 -E7 and LALF-E7-GFP polypeptides form PB-like structures when targeted to chloroplasts, which are more concentrated and abundant than for the cytoplasmic versions. These results could explain why LALF 32-51 -E7 accumulated to much higher levels when targeted to the chloroplasts than when localized in the cytoplasm in our vaccine production feasibility study (Yanez et al, 2017). This study was a proof of concept that confirms the importance of subcellular localization, and which further highlights that chloroplasts are a useful compartment to which to target recombinant proteins.…”
Section: Discussionsupporting
confidence: 59%
“…We targeted it to the chloroplasts to determine whether that would enhance accumulation, as we previously detected only very low expression levels when the protein was targeted to the cytoplasm. Indeed, LALF 32‐51 ‐E7 accumulated to higher levels when targeted to the chloroplasts of N. benthamiana leaves (up to 0.56% of total soluble proteins, TSP) than when not targeted to any cell compartment (up to 0.017% TSP) (Yanez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, coexpression of HPV16 L1 and L2 genes encoding the major and minor coat proteins, respectively, resulted in the accumulation of 1710 mg HPV16 VLPs per kg (fw) of plant biomass (Pineo et al 2013). In other studies, Yanez et al (2017Yanez et al ( , 2018 demonstrated the production of HPV16 E7 to high levels in plants. Together, these studies demonstrate that transient transgene expression, followed by protein import into chloroplasts, is a powerful approach for high-level recombinant protein production in plants.…”
Section: Transient Expression Of Foreign Proteinsmentioning
confidence: 99%
“…Among these, vaccines against influenza viruses H5N1, HAI-05, and H1N1 produced in N. benthamiana and an edible vaccine to treat the hepatitis B virus expressed in tobacco are under clinical trials [ 62 , 63 , 64 , 65 ]. More recently, the VP40 antigen of Zaire ebolavirus was produced in N. tobacum and maintained its antigenicity and the ability to induce immune response in mice [ 66 ]; a candidate therapeutic vaccine against papillomavirus, consisting of the oncoprotein E7 fused with a bacterial cell-penetrating peptide, was expressed in N. benthamiana [ 67 ]; a synthetic gene expressed in tobacco and encoding for a capsid protein of the food and mouth disease virus was able to stimulate the immunogenic response in rabbits [ 56 ]; a recombinant vaccine for classical swine fever virus was produced at a cost-effective large scale in N. benthamiana [ 57 ]; a full-length hepatitis C virus glycoprotein E2, correctly processed and folded, was expressed in N. benthamiana and induced immune response in vaccinated mice [ 68 ].…”
Section: Suitable Plant Species For Vaccine Productionmentioning
confidence: 99%